20082ee131A_1_HW8SO

20082ee131A_1_HW8SO - EE 131A Homework #8 Solution Spring...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: EE 131A Homework #8 Solution Spring 2008 K. Yao 1. E { X | Y = 1 } = 3; E { X | Y = 2 } = 5 + E { X } ; E { X | Y = 3 } = 7 + E { X } . Thus, E { X } = 1 3 (3 + 5 + E { X } + 7 + E { X } ) or E { X } = 15 . 2. E { XY } = Z { Z x 2 ye- 2 x dy } dx = (3) / 8 = 1 / 4 . f X ( x ) = Z x (2 /x ) e- 2 x dy = 2 e- 2 x , x < ; E { X } = Z xf X ( x ) dx = 1 / 2 . f Y ( y ) = Z y (2 /x ) e- 2 x dx, y < ; E { Y } = Z o yf Y ( y ) dy = (2) / 4 = 1 / 4 . cov ( X,Y ) = E { XY } - E { X } E { Y } = 1 / 4- (1 / 2)(1 / 4) = 1 / 8 . 3. (a) f N ( n ) = P ( N = n ) = 1 / 3 for n = 1 , 2 , 3 X | N is uniform. so f ( x | n ) = 1 /n for 0 x n ; n = 1 , 2 , 3 f ( x,n ) = f ( n ) f ( x | n ) = 1 / (3 n ) for 0 x n ; n = 1 , 2 , 3 f ( x ) = 3 n =1 f ( n,x ) But the number of non-zero terms in the sum depends on x . Case 1. 0 x 1 f ( x ) = f (1 ,x ) + f (2 ,x ) + f (3 ,x ) = 1 / 3 + 1 / (3 2) + 1 / (3 3) = 11 / 18 Case 2. 1 < x 2 f ( x ) = f (2 ,x ) + f (3 ,x ) = 1 / (3 2) + 1 / (3 3) = 5 /...
View Full Document

Page1 / 3

20082ee131A_1_HW8SO - EE 131A Homework #8 Solution Spring...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online